Religiosity and spirituality in patients with epilepsy - Rigon, Isadora Barazzetti; Calado, Gabriel de Almeida; Linhares, Lucas Savaris; Cantu, Pietro Lentz Martins; Moritz, Jorge Luis Wollstein; Wolf, Peter; Lin, Katia (Arquivos de Neuro-Psiquiatria, 2019)
Religiosity and spirituality (R/S) are widely regarded as important allies against illness and suffering in general. Findings in temporal lobe epilepsy (TLE) suggest the temporal lobe as the anatomical-functional basis of religious experiences. Both R/S are relevant in patients with epilepsy (PWE) since epilepsy can lead to psychosocial issues for a significant portion of patients and their families.Objective: To investigate R/S in PWE, as well as the impact of different epileptic syndromes on patients' R/S.Methods: One hundred PWE and 50 healthy volunteers matched for age, sex and educational level were submitted to an interview, as well as three previously validated questionnaires: Index of Core Spiritual Experience (INSPIRIT-R), Hospital Anxiety and Depression Scale (HADS), and the Quality of Life in Epilepsy Inventory (QOLIE-31).Results: PWE's and control's mean ages were 35.9 ± 12.4 vs. 36.3 ± 18.1 years, mean schooling was 8.9 ± 3.7 vs. 10.1 ± 4.2 years. The mean age of epilepsy onset was 14.5 ± 12.1 and monthly frequency of seizures was 5.9 ± 12.6. INSPIRIT-R's scores were not statistically significantly different between patients and controls (3.0 ± 0.8 vs. 3.0 ± 0.8); however, INSPIRIT-R's scores were significantly higher in TLE patients when compared with other epilepsy syndromes (3.2 ± 0.7 vs. 2.8 ± 0.9; p = 0.04).Conclusion: Temporal lobe epilepsy patients have higher levels of R/S.
Keywords: Epilepsy, temporal lobe; quality of life; spirituality